The Transition to Outcome-Based Education (OBE): A Phenomenological Study of Islamic Religious Education Lecturers - Purnomo; Budiyono Saputro; Miftahuddin (Academia Publication, 2026)
This study aims to explore in depth the understanding, challenges, and support experienced by Islamic Religious Education (IRE) lecturers during the transition to the Outcome-Based Education (OBE) curriculum, which often faces skepticism and technical challenges. This study employs a qualitative approach with a phenomenological design to explore the meaning of the lived experiences of four lecturers from the IRE study program. Data were collected through in-depth interviews and analyzed using a framework analysis based on Kurt Lewin's Three Phases of Change Model (Unfreeze, Change, Refreeze), and enriched with Hochschild's Emotional Labor Theory. The research findings indicate that the OBE transition experienced a systemic failure in the Refreeze Phase. The Unfreeze Phase successfully created cognitive dissonance about the need for change, but immediately triggered negative emotional labor such as